ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN LEVERAGE TERHADAP COST OF EQUITY PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010 – 2012 - B51110085, Lindy Wati (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This research aims to determine the effect of the cost of equity for broad disclosure of corporate social responsibility (CSR). Cost of equity is measured from the rate of return produced by the company. The population of this research were 14 companies in the food and beverage sector are listed on the Stock Exchange in 2010-2012. Purposive sampling method was obtained by 4 companies with a data source in the form of annual reports issued by each company for 3 years. Data was analyzed using content analysis. Data processing was performed with the classical assumption, whereas hypothesis testing performed by multiple linear regression analysis. The results showed that the cost of equity affects the broad disclosure of CSR but less significant with a value of coefficient of determination equal to 5%. Keywords: Corporate Social Responsibility (CSR), Cost of Equity